2011
DOI: 10.2147/ijn.s15057
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Pluronic® F127-based hydrogel containing liposomes for the controlled delivery of paclitaxel: in vitro drug release, cell cytotoxicity, and uptake studies

Abstract: Purpose To develop an in situ gel system comprising liposome-containing paclitaxel (PTX) dispersed within the thermoreversible gel (Pluronic ® F127 gel) for controlled release and improved antitumor drug efficiency. Methods The dialysis membrane and membrane-less diffusion method were used to investigate the in vitro drug release behavior. Differential scanning calorimetry (DSC) thermal analysis was used to investigate the “micellization” and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 68 publications
7
54
1
Order By: Relevance
“…In this study, animals received a single dose of PTX-CrEL, and it is possible that only a subtherapeutic level of PTX reached the metastatic sites in bone, stimulating the proliferation of cancer cells, as some teams have reported [54, 55]. Unlike PTX-CrEL (PTX release of 70% in 4 hours and 100% in 12 hours) [56], PTX-NPs provided a continuous localized dose of PTX (~0.7% per day), thus providing the comparison between fast- and sustained-release formulations of PTX on their efficacy. NP albumin-bound (nab) PTX, despite having smaller particle size (~130 nm) than the openings of the bone marrow capillary fenestrations (~170 nm), has in fact been shown to increase the incidence of metastasis, including to bones, in an animal model of breast cancer metastasis [57].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, animals received a single dose of PTX-CrEL, and it is possible that only a subtherapeutic level of PTX reached the metastatic sites in bone, stimulating the proliferation of cancer cells, as some teams have reported [54, 55]. Unlike PTX-CrEL (PTX release of 70% in 4 hours and 100% in 12 hours) [56], PTX-NPs provided a continuous localized dose of PTX (~0.7% per day), thus providing the comparison between fast- and sustained-release formulations of PTX on their efficacy. NP albumin-bound (nab) PTX, despite having smaller particle size (~130 nm) than the openings of the bone marrow capillary fenestrations (~170 nm), has in fact been shown to increase the incidence of metastasis, including to bones, in an animal model of breast cancer metastasis [57].…”
Section: Discussionmentioning
confidence: 99%
“…A representative class of amphiphilic block copolymers is triblock copolymers formed from poly(ethylene oxide) (PEO) and poly(propylene oxide) (PPO), also known as Pluronics or poloxamers 1 . Poloxamers have been used as versatile biomaterials such as thermosensitive hydrogels 2,3 , drug delivery carriers 4,5 , and chemosensitization agents for cancer therapy 68 . Poloxamer 188 (P188), an 8400 g/mol PEO-PPO-PEO triblock copolymer comprising two segments of 75 PEO units on either side of a segment with 30 PPO units, has demonstrated membrane stabilization characteristics in multiple scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Caicco et al [38] observed that poly(lactic-co-gycolic) acid microsphere-encapsulated cyclosporine A (CsA) released from hyaluronan-methylcellulose hydrogel was prolonged for a period 3-4 weeks following epi-cortical delivery in vivo , whereas particulate CsA extended release to days from hours for solubilized CsA [38]. Nie et al [36] formulated the anticancer drug, paclitaxel (PTX), into liposomal nanoparticles in PF-127 hydrogel to achieve the desired drug release rate. They found that drug release was significantly prolonged from liposomal-encapsulated PTX immobilized within PF-127 hydrogel compared to liposomal PTX alone or PTX in PF-127, leading to substantial cytotoxic benefit in a cancer cell line [36].…”
Section: Discussionmentioning
confidence: 99%
“…Nie et al [36] formulated the anticancer drug, paclitaxel (PTX), into liposomal nanoparticles in PF-127 hydrogel to achieve the desired drug release rate. They found that drug release was significantly prolonged from liposomal-encapsulated PTX immobilized within PF-127 hydrogel compared to liposomal PTX alone or PTX in PF-127, leading to substantial cytotoxic benefit in a cancer cell line [36]. Liposomes may act as a reservoir for sustained drug release and PF-127 may enhance penetration of liposomal drugs to improve their efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation